Computer-aided design system for technical and economical comparison of crane electrical drives - Gerasymiak, Rostyslav; Busher, Viktor; Shvets, Liudmyla; Savich, Svitlana (Publishing House of Lviv Polytechnic National University, 2012)
Computer-aided design system for technical and economic comparison of crane electrical drives, considering the ratio of static and dynamic modes, load and moment inertia, relative running time with reduced speed, is designed. The computer-aided design system provides an opportunity to make a better informed decision about the choice or upgrading of electrical drives. Розроблено програмний комплекс для техніко-економічного порівняння кранових електроприводів з урахуванням співвідношення статичних і динамічних режимів, навантаження і моментів інерції, відносного часу роботи зі зниженою швидкістю. Це надає змогу прийняти зважене рішення щодо вибору або реконструкції електропривода.
Програмний комплекс для техніко-економічного порівняння кранових електроприводів
Keywords: CAD; induction motor electrodrive; technical and economical comparison